SUBSTITUSI PATI SAGU DENGAN TEPUNG BIJI NANGKA DALAM PEMBUATAN MI INSTAN - Hafpis ' Hasroni; Faizah ' Hamzah; Akhyar ' Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sago starch instan noodle was maked with jackfruit seed flour as additional compotition. Experiment was chosen in this research with 4 treatment and 4 time reply. Combination of sago starch with jackfruit seed flour was SNP1 (95%-5%), SNP2 (90%-10%), SNP3 (85-15%), SNP4 (80%-20%). The observation include on moisture content, ash content, proteint content, fiber content, rehydration time, integrity, and sensory. The data was analyzed of variance. Result of this reseach was SNP3 as the best combination of compotition, moisture content (8,12%), ash content (2,48%), protein content (3,86%), rehydrate on time (3,24 minutes), witachness (90,75%), and sensory with a slightly brown, flovourful meat of jackfruit, jackfruit seed taste, slightly chewy texture and panelists expessed the impression like. Keywords: Sago starch, jackfruit seeds flour, instant noodles